An analytical method for finding exact solutions of modified Korteweg–de Vries equation - Md. Shafiqul Islam; Kamruzzaman Khan; M. Ali Akbar (Results in Physics, 2015)
In this present work, we have studied new extension of the (G′/G)-expansion method for finding the solitary wave solutions of the modified Korteweg–de Vries (mKdV) equation. It has been shown that the proposed method is effective and can be used for many other nonlinear evolution equations (NLEEs) in mathematical physics. The obtained results show that the method is very powerful and convenient mathematical tool for nonlinear evolution equations in science and engineering.